Effects of Nano-kaolin clay on the rutting resistance of asphalt binder - Putra Jaya, Ramadhansyah; Nurulain, C. M.; Norhidayah, Abdul Hassan; Nordiana, Mashros; Haryati, Yaacob; Mohd Rosli, Hainin; Mohd Khairul Idham, Mohd Satar; Mohamad Idris, Ali (AIP Publishing, 2019)
Nowadays, nanotechnology has been widely study because it’s proven to improve the properties of asphalt. There a lot of nano-materials in industrial area and one of them are Nano clay. Therefore, this study was performed to investigate the rutting resistance of asphalt incorporating Nano-kaolin. The asphalt was evaluated in fresh and aged condition. In this study, asphalt binders with five different percentages of Nano-kaolin (0%, 3%, 5%, 7%, and 9%) contain was prepared. The results indicated that the addition of Nano-kaolin was helpful in enhance the rutting resistance of the binders. In addition, based on the testing results, the ideal asphalt was achieved at 5% of Nano-kaolin content.